Two Moments in the Biography of Qedushah (a.k.a. Holiness). (July 2022) - Stern, Josef
Abstract: This paper analyzes two transformative conceptions of qedushah (holiness) in medieval Jewish thought, Moses Maimonides's and Moses Nahmanides's. Maimonides reduces qedushah to the Mosaic commandments which he reconceives as communal institutions to constrain bodily desires and promote intellectualist values and as training for perfected individuals to de-corporealize themselves in imitation of God. Nahmanides argues that Maimonides's legal reduction of qedushah leads to the absurd conclusion that the perfectly scrupulous law-abiding scoundrel who exploits loopholes in the law is qadosh ! He therefore reconceives qedushah as a complement to the Mosaic commandments intended to counter the problem of the scoundrel. Thus qedushah is re-born as a corrective to abuse of the Law. Nahmanides then proposes two ways to achieve this goal: i) by rabbinic enactment of more laws to fill in (loop) holes in the Law and ii) by cultivating a virtue-oriented, non-legal conception of holiness as a character-trait that leads agents to act properly and spontaneously without legislation. For Maimonides the ultimate state of qedushah is the dis-embodied state of the intellect, for Nahmanides it is a state in which the whole person, body and soul, clings to the deity.